1.
а)2(х2-2х+3)-3(2х2+х-1)
2*3-3(4х+х-1)
6-3(5х-1)
6-15х+3
9-15х
b)-4b(b2-2b)-2b(3b-b2)
-4b*0-2b(3b-2b)
0-2b*b
-2b^2
c)4(2x-3y)-(2x+5y)+3(y-2x)
4(2x-3y)-(2x+5y)+3(y-2x)
8x-12y-2x-5y+3y-6x
0-14y
-14y
2.
a)2(1-3x)=14
1-3x=7
-3x=7-1
-3x=6
x=-2
b)8-3(y-2)=4
8-3y+6=4
14-3y=4
-3y=4-14
-3y=-10
y=10/3
c)2(x-3)+4(x+3)=0
2x-6+4x+12=0
6x+6=0
6x=-6
x=-1
d)y(2-3y)+3y(1+y)=15
y(2-3y)+3y(1+y)=15
2y-3y^2+3y+3y^2=15
5y=15
y=3
e)2(x-1)-3=5(2x-1)-7x
2x-2-3=10x-5-7x
2x-5=3x-5
2x=3x
2x-3x=0
-x=0
x=0
f)2x(6x-2)=7x(2x-4)-2x2
12x^2-4x=14x^2-28x-4x
12x^2=14x^2-28x
12x^2-14x^2+28x=0
-2x^2+28x=0
-2x(x-14)=0
x(x-14)=0
x=0 x-14=0
x=0 x=14
№1 (x-1)(x+5)(x^2+4)=0
произведение равно 0, если один из множителей равен 0
x-1=0; x+5=0; x^2+4=0
x=1 x=-5 x^2=-4
корней нет
ответ: x=1, x=-5
№2 12x^2=0
произведение равно 0, если один из множителей равен 0
x^2=0
x=0
ответ: x=0
№3 x^2+64=0
x^2=-64
ответ: корней нет
№4 x^2-64=0
x^2=64
x=
x=8
ответ: 8